My Dear Boy : Carrie Hughes's Letters to Langston Hughes, 1926-1938 - Hughes, Carrie, -1938 (Book collections on Project MUSE., 2013)
"Tidwell and Williams analyze the causal relationships in her interactions with Langston and other family members through the use of psychiatrist Murray Bowen's Family Systems Theory (FST). ... The editors have grouped the 250 letters chronologically into four sections, each preceded by a brief contextual introduction"--